2008
DOI: 10.1007/s00436-008-0878-7
|View full text |Cite
|
Sign up to set email alerts
|

Factors in the resistance of rats to re-infection and super-infection by Clonorchis sinensis

Abstract: Rats develop resistance to re-infection by Clonorchis sinensis while humans do not. We investigated factors involved in the development of resistance to re-infection and super-infection in rats. Sprague-Dawley rats were infected by C. sinensis metacercariae and treated with praziquantel, then re-infected after immune modulation. The rats were also subjected to super-imposed infection after primary infection. Resistance to re-infection was observed by lowered rates of worm recovery after various durations from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 19 publications
1
9
0
Order By: Relevance
“…Nine rats were successfully found with one adult worm in extrahepatic bile duct and with pathological changes (infection rate was 90%, data not published). The infection rate will be higher for human beings than rats, for rats were known to highly resist C. sinensis during reinfection (Sohn et al 2006;Zhang et al 2008); whereas, human develops immunotolerance to C. sinensis. Up to now, little was reported about the least infection dose of pathogens.…”
Section: Discussionmentioning
confidence: 98%
“…Nine rats were successfully found with one adult worm in extrahepatic bile duct and with pathological changes (infection rate was 90%, data not published). The infection rate will be higher for human beings than rats, for rats were known to highly resist C. sinensis during reinfection (Sohn et al 2006;Zhang et al 2008); whereas, human develops immunotolerance to C. sinensis. Up to now, little was reported about the least infection dose of pathogens.…”
Section: Discussionmentioning
confidence: 98%
“…This finding suggests that previous infection affords poor protection against reinfection or super-infection in humans. However, rats are known to develop near-complete resistance to re-infection or superinfection by C. sinensis [7,8]. Although the mechanism of resistance to re-infection is unknown, it has been suggested to involve an immune-related host response [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…However, rats are known to develop near-complete resistance to re-infection or superinfection by C. sinensis [7,8]. Although the mechanism of resistance to re-infection is unknown, it has been suggested to involve an immune-related host response [8,9]. It was observed that rats immunized with crude antigens of C. sinensis had high serum IgG levels but exhibited no protection against infection [10].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations